The use of social media as a two-way mirror for narcissistic adolescents from Austria, Belgium, South-Korea, and Spain. - Lluís Mas Manchón; David Badajoz Dávila (PLoS ONE, 2022)
The use of social networking sites (SNS or social media) often comes with strong self-centered behaviors to promote self-appearance. The relationship between narcissism and social media use has intensively occupied scholars in the last decade, yet not much research has focused on, first, how the intensity of social media use (SNS use) is associated with narcissism through a self-centered appearance focused use of these SNS; and second, whether these associations are moderated or not by cultural differences of the country of origin in such a critical age of personality formation and (global) culturalization as the transition from pre-adolescence to adolescence. We performed a correlation and mediation analysis on a cross-sectional survey among Austrian, Belgian, Spanish, and South Korean adolescents (n = 1,983; Mage 14.41, 50.3% boys) examining the adolescents' daily usage of social media, their self-centered appearance focused behavior, and the reported narcissism. Findings show that a self-centered appearance focused use of SNS (SCA) moderates the association between SNS use and narcissism, especially for males from the three European countries. We have also particularly found that the years of use, number of friends and time spent in FB are associated with narcissism. Since SCA is defined in the study as narcissistic behavior in SNS, we argue that social media are part of the socialization process as both reinforcers and catalyzers of narcissism.